A molecular dynamics study of water vapor nucleation in the presence of ions. (1st December 2015) - Zhang, Chao; Wang, Yueshe; Liu, Yingwen; Yang, Yang
Abstract: Ions make a significant contribution to the nucleation dynamics of aqueous aerosol particles, but the understanding about microscopic mechanism is insufficient. In this paper, molecular dynamics simulations are conducted to investigate the condensation of supersaturated water vapor in the presence and absence of ions. The Yasuoka–Matsumoto (YM) method and the kinetic analysis are extended to investigate the influence of ions on the nucleation dynamics. It is observed that the presence of ions has a dramatic influence on the water vapor nucleation, which makes the clustering of water molecules easily. The ion concentration and the supersaturation are key factors that control the phase transition in the simulation system. For a certain supersaturation, the generation rate of clusters is proportional to the ion density. Water molecules tend to condense around ions with negative charge and high electric quantity. In addition, details of the cluster change are explored by the kinetic analysis when the system is added with cations and anions simultaneously. It is found that the change rate of the cluster increases with the rise of ions and decreases with the rise of water molecules. This phenomenon can be related to the microscopic structure of clusters that water molecules wrap around the ions to form a shell. The coalescence effect plays an important role in the nucleation process, and the proportion of the coalescence effect increases as the increase of supersaturation. Graphical abstract: Highlights: Yasuoka–Matsumoto method is extended to study the effect of ions on nucleation. H2 O prefer to condense around ion with negative charge and high electric quantity. Phase transition in system is controlled by supersaturation and ion concentration. Change rate of clusters is related to the microscopic structure. Coalescence effect plays an important role in the ion-induced nucleation process.